Študija dinamičnih karakteristik sklopa radialnega rotorja in vležajenja ventilatorja hladilnega sistema borbenih vozil M 84 in T 72 - Širok, Brane (Strojniški vestnik, 1999)
Combat vehicles like the M 84 tank are exposed to extreme mechanical loading when driving and shooting. All the mechanical parts are therefore designed for extreme loading. Loading determination is strongly connected to determination of its dynamic properties in the examined components. With a newly developed rotor for a cooling fan with bearings, mechanical loading was tested and analyzed on a test rig. Experimental work and dynamic analysis are presented in the paper. The most suitable bearing type is selected and criteria of allowed loading of the fan are presented in the conclusion.
Keywords: ventilatorji; uležajenje rotorjev; analize dinamične; karakteristike; rotorji; hlajenje; ležaji